The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/6648182
|View full text |Cite
|
Sign up to set email alerts
|

L Antigen Family Member 3 Serves as a Prognostic Biomarker for the Clinical Outcome and Immune Infiltration in Skin Cutaneous Melanoma

Abstract: L Antigen Family Member 3 (LAGE3) is an important RNA modification-related protein. Whereas few studies have interrogated the LAGE3 protein, there is limited data on its role in tumors. Here, we analyzed and profiled the LAGE3 protein in skin cutaneous melanoma (CM) using TCGA, GTEx, or GEO databases. Our data showed an upregulation of LAGE3 in melanoma cell lines compared to normal skin cell lines. Besides, the Kaplan–Meier curves and Cox proportional hazard model revealed that LAGE3 was an independent surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Combined with the finding that LAGE3 is highly conserved and is activated in numerous human tumors, it indicates that its encoded protein is functionally pivotal in the progression of cancers [9]. LAGE3 serves as a prognostic biomarker for the clinical outcome and immune infiltration in skin cutaneous melanoma [23]. Moreover, previous studies have demonstrated that LAGE3 is highly overexpressed in various cancers.…”
Section: Discussionmentioning
confidence: 92%
“…Combined with the finding that LAGE3 is highly conserved and is activated in numerous human tumors, it indicates that its encoded protein is functionally pivotal in the progression of cancers [9]. LAGE3 serves as a prognostic biomarker for the clinical outcome and immune infiltration in skin cutaneous melanoma [23]. Moreover, previous studies have demonstrated that LAGE3 is highly overexpressed in various cancers.…”
Section: Discussionmentioning
confidence: 92%
“…Recombinant human L antigen family member 3 (LAGE3) is a part of the CTAG family ubiquitously expressed in many cell types and is often considered a notable up-regulated RNA modification-related protein in a majority of carcinoma cases [ 4 ]. Previous studies have consistently observed that an extensive expression of LAGE3 is associated with poor prognosis and poor immune infiltration in patients with papillary thyroid carcinoma (PTC) and cutaneous melanoma (CM) [ 5 8 ]. Dong X et al found that LAGE3 enhanced the abilities of proliferation, migration, and invasion of cancer cells and resisted their apoptosis by activating intrinsic intracellular signaling pathways, thereby facilitating the development of breast cancer (BC) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances in targeted therapies and novel immunotherapies ( 6 , 7 ), the efficacy of all treatments is greatly compromised as compared to active surgical treatment, which is very effective in the early stages of the disease. Thus, there is a need to identify biomarkers that are related to tumors in conjunction with stages that affect prognosis ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%